2(7+n)=-10

Simple and best practice solution for 2(7+n)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7+n)=-10 equation:


Simplifying
2(7 + n) = -10
(7 * 2 + n * 2) = -10
(14 + 2n) = -10

Solving
14 + 2n = -10

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 2n = -10 + -14

Combine like terms: 14 + -14 = 0
0 + 2n = -10 + -14
2n = -10 + -14

Combine like terms: -10 + -14 = -24
2n = -24

Divide each side by '2'.
n = -12

Simplifying
n = -12

See similar equations:

| 7x^2+100x-24=0 | | x+7-x=-5 | | x+20=2x+80 | | 45+90x=855 | | 5x+252=14x-9 | | 30-6x=12-8x | | 6t^2=-t+2 | | 7X+3Y+36=0 | | 12m+8-5m+2+m=6(m-1) | | -4x^2+50x-150=0 | | 7x+(7x+1)+(8x+3)=180 | | 0.4x-9.5(x-1)=55 | | 6a+10a^2=0 | | 2(a-7)-3a=-17-(a-3) | | 6x^2+50x+100=0 | | 12s+9t=57 | | 4x+(12)=8 | | 3a-10=25 | | 8(-2m-7)+8(-5+m)=4m-6m | | 3z+2(6-z)=-(z-1)+1 | | 3a-10=-25 | | 28*x=(4x-2)*7 | | 5-8x+x=40 | | d(3d-15)=0 | | Y=.5+8 | | -8m-[2(10-5m)+15]=9m | | 45a^4b^3/15a^4b^2 | | r^2+81=r^2+6r+9 | | 2(7c-1)-18=12c+2 | | 7.4X=-52.54 | | -4.6X+1.1=-21.9 | | 2(c-1)-18=12c+2 |

Equations solver categories